Flexible Modulation of CO‐Release Using Various Nuclearity of Metal Carbonyl Clusters on Graphene Oxide for Stroke Remediation. Issue 5 (12th January 2018) - Tan, Mein Jin; Pan, Han‐Chi; Tan, Hui Ru; Chai, Jian Wei; Lim, Qi Feng; Wong, Ten It; Zhou, Xiaodong; Hong, Zi‐Yao; Liao, Lun‐De; Kong, Kien Voon
Abstract: Utilizing the size‐dependent adsorption properties of ruthenium carbonyl clusters (Ru–carbon monoxide (CO)) onto graphene oxide (GO), a facile CO‐release platform for in situ vasodilation as a treatment for stroke‐related vascular diseases is developed. The rate and amount of formation of the CO‐release‐active Ru II (CO)2 species can be modulated by a simple mixing procedure at room temperature. The subsequent thermally induced oxidation of Ru II (CO)2 to RuO2 on the GO surface results in the release of CO. Further modulation of thermal and CO‐release properties can be achieved via a hybridization of medium‐ and high‐nuclearity of Ru–CO clusters that produces a RuO2 /Ru II (CO)2 / 6 Ru–CO–GO composite, where 6 Ru–CO–GO provides a photothermally activated reservoir of Ru II (CO)2 species and the combined infrared absorption properties of GO and RuO2 provides photothermal response for in situ CO‐release. The RuO2 /Ru II (CO)2 / 6 Ru–CO–GO composite does not produce any cytotoxicity and the efficacy of the composite is further demonstrated in a cortical photothrombotic ischemia rat model. Abstract : By utilizing the size‐dependent adsorption properties of Ru–carbon monoxide (CO) compounds with graphene oxide (GO), a facile method for the modulation of Ru II (CO)2 for treatment of vascular‐related stroke disease is demonstrated. The hybridization of medium‐ and high‐nuclearity ruthenium carbonyl compounds with GO produces a biocompatible CO‐release material with excellent infrared triggerable photothermal properties.